Aesthetic, philosophical, human, moral and religious dimensions In the epics "The Iliad" and "Odyssey" by Homer A call for peace and rejection of war (Damascus University Journal of arts and humanities sciences, 2022)
The "Iliad" and "Odyssey" are Homer's two epic epics. They were and are a rich source for many creators and readers.This study attempts to approach Homer's philosophical and cosmic vision by examining the aesthetic, philosophical, human, and religious dimensions of these two epics. This study was not free from answering some questions that concern readers and researchers in the area of ​​global and comparative studies. In addition, some of the errors mentioned in the two epics that readers and scholars used to circulate without meditation and reflection have been corrected. For example: the real causes of the war between the Greeks and Trojans, the reasons for Achelius' anger and the length of the war, which lasted twenty years rather than ten years, as mentioned in the two epics. And Odysseus' absence from his home in Ithaca lasted for thirty years, not twenty, Homer notes. The study found that the two epics deal with one topic, "The Story of Odysseus", and not with two separate topics. The study concluded that these two epics have a deep humanistic vision - perhaps Homer thought about it and wanted it as they searched for it - the call to peace and the rejection of war.
Keywords: Aesthetic, philosophical, human, moral and religious dimensions In the epics